Теорія і методи комп’ютерного опрацювання біосигналів на основі машинного навчання - Хома, Юрій Володимирович (Національний університет "Львівська політехніка", 2020)
У дисертаційній роботі вирішено актуальну науково-прикладну проблему у галузі інструментального забезпечення біоінформатики – розвиток теоретичних засад і нових підходів до удосконалення комп’ютерних систем опрацювання біосигналів на основі широкого використання штучних нейромереж і технологій глибинного навчання. Представлено концепцію трьох системних рівнів комп’ютерного опрацювання біосигналів, що базується на чіткому розмежуванні функцій системних рівнів від методів і засобів, що їх реалізують. Таке розділення сприяє структуризації знань, уможливлює оцінювання ефективності різних методів і вибір кращих проектних рішень із урахуванням специфіки завдань, умов і сценаріїв. Автоматизовано пошук оптимальних значень гіперпараметрів багатошарового нейрокласифікатора шляхом використання простої прогностичної моделі машинного навчання. Це дає змогу на 4 порядки скоротити час пошуку порівняно із повним перебором в просторі можливих значень. Розроблено і апробовано підхід до виявлення і коригування залишкових аномалій в біосигналах, який базується на застосуванні нейромережевих автоенкодерів для нелінійної фільтрації завад, зосереджених в тій самій частині спектру, що й корисний сигнал. Застосування підходу у 5-7 разів зменшує похибку ідентифікації. Результати роботи можуть бути застосовані до різних прикладних задач, у таких сферах як кібербезпека та системи доступу (біометрична ідентифікація), робототехніка (нейромережеві інтерфейси управління) і афективна інформатика (аналіз психоемоційного стану), а також у медицині (діагностика, клінічні дослідження тощо). В диссертационной работе решена актуальная научно-прикладная проблема в области инструментального обеспечения биоинформатики - развитие теоретических основ и новых подходов к совершенствованию компьютерных систем обработки биосигналов на основе широкого использования искусственных нейронных сетей и технологий глубинного обучения. Представлена концепция трех системных уровней компьютерной обработки биосигналов, основанная на четком разграничении функций системных уровней от методов и средств, которые используются для их реализации. Такое разделение способствует структуризации знаний, позволяет оценить эффективность различных методов и выбрать лучшие проектные решения с учетом специфики задач, условий и сценариев. Автоматизирован поиск оптимальных значений гиперпараметров многослойного нейроклассификатора путем использования простой прогностической модели машинного обучения. Это позволяет на 4 порядка сократить время поиска по сравнению с полным перебором в пространстве всех возможных значений. Разработан и апробирован подход к выявлению и коррекции остаточных аномалий в биосигналах, основанный на применении нейросетевых автоэнкодеров для нелинейной фильтрации помех, сосредоточенных в той же части спектра, и полезный сигнал. Применение коррекции аномалий в 5-7 раз уменьшает погрешность идентификации. Результаты работы могут быть применены в различных направлениях, таких как компьютерная безопасность и системы доступа (биометрическая идентификация), робототехника (нейросетевые интерфейсы управления) и аффективная информатика (анализ психоэмоционального состояния), а также в медицине (диагностика, клинические исследования и т.п.). The thesis solves a scientific problem in the field of instrumental support of bioinformatics - the development of theoretical foundations, improvement of methodological, algorithmic, software, and technical basis of the computer systems for processing of biosignals and data based on the extensive use of artificial neural networks and deep learning technologies. Current state and future perspectives of machine learning usage in the computer bioinformatics systems are analyzed in the thesis. It is shown that the heterogeneousness of data and a wide range of bioinformatics tasks influenced the development of specialized solutions for each separate domain or application. This complicates the possibility to compare the effectiveness of certain methods as well as the usage of the best system design variants for the new tasks. A novel framework related to the development of principles for the design of the biosignals computer processing systems involving a combination of machine learning techniques and digital signal processing is presented in the thesis. The expediency of separation of the system levels within the process of biosignals processing is reasoned, and their functions are outlined. Innovativeness of the suggested approach lies in the separation of functions of the lower, middle, and upper levels from methods with the help of which they are realized, as well as from the implementation variants for these methods based on the hardware and software components. The middle system level is significantly invariable both in regards to the task to be solved and to the biosignal type. At the same time, the upper level is specific as to the final application, and the lower level is specific as to the type of biosignal. Distinct outlining of functions for each system level and the inter-level interfaces opens perspectives for information structuring during the analysis of the known decisions, which simplifies the analysis and comparison of the effectiveness of these solutions. The design process of the computer system for the specific tasks gets simplified and potentially quickens due to the possibility of transferring the best results among the related tasks. On the basis of the developed three system levels concept the range of tasks related to machine learning application and biosignals processing on all the system levels was studied and analyzed. A novel method of optimal hyperparameters selection for a multilayer neural network classifier based on the Monte Carlo method and predictive modeling was developed and introduced in the thesis, new algorithms for detection and correction of anomalies in ECG-signals were presented as well. This resulted in reduction of hyperparameters optimization time by 4 orders compared to a grid search approach in the entire hyperspace of possible values. A new approach to the detection and correction of residual anomalies in biosignals was developed and tested. This approach is based on the use of neural network autoencoders for nonlinear filtering of distortions that are located in the same spectral band as the useful signal and its application reduces identification error by 5-7 times. A method of software conditioning of biosignals was developed, which enabled parameters unification of digital records of biosignals from open databases by resampling, rescaling, time normalization, etc. and its application improves the issue of low data volume while deep neural networks training. A comprehensive study of the influence of the variability of ECG signal acquisition systems (different data sets, sampling frequency, recording duration, data volume) on the accuracy of biometric identification was performed. The obtained results proved sufficient stability and reliability of the electrocardiogram as a biometric marker and confirmed the possibility of its real-world application in biometric identification systems. Neural network equalizer was designed for dynamical error correction of bioimpedance sensors, which resulted in expanding the operating frequency band up to 100 times. Functionality was expanded, metrological characteristics were improved and the speed of the digital rheograph was doubled by improving the Howland current pump by compensating the basic bioimpedance with a coded potentiometer (trimmer) and using a direct digital synthesis of orthogonal probing signals. Intelligent processing of vibroarthrography signals based on a combination of machine learning algorithms and wavelet decomposition was developed, which allowed to achieve better accuracy in terms of knee joint disorders analysis. The results of the work can be used in various applications, such as cybersecurity and access systems (biometric identification), robotics (bio-machine control interfaces), and affective informatics (psycho-emotional state analysis), as well as a medical domain (diagnostics, clinical trials).
Теория и методы компьютерной обработки биосигналов на основе машинного обучения
Theory and methods of computer processing of biosignals based on machine learning
Keywords: комп’ютерна біоінформатична система; біосигнали; біометрична ідентифікація; нейрокомп'ютерні інтерфейси; вимірювальні перетворювачі імпедансу; цифрове опрацювання сигналів; цифровий еквалайзер; алгоритми коригування аномалій; машинне навчання; класифікація; штучні нейронні мережі; автоенкодери; компьютерная биоинформационная система; биосигналы; биометрическая идентификация; нейрокомпьютерные интерфейсы; измерительные преобразователи импеданса; цифровая обработка сигналов; цифровой эквалайзер; алгоритмы коррекции аномалий; машинное обучение; классификация; искусственные нейронные сети; автоенкодеры; computer bioinformatics system; biosignals; biometric identification; brain computer interfaces; impedance measuring converters; digital signal processing; digital equalizer; anomaly correction algorithms; machine learning; classification; artificial neural networks; autoencoders; 621.382: 681.58:681.32